KONSEP LUAS PADA BANGUN DATAR BAGI GURU KELAS V DI SD PELITA 2, JAKARTA BARAT - Manurung, Alberth Supriyanto (Jurnal Pengabdian Masyarakat AbdiMas, 2018)
AbstractThe intelligence of an elementary school teacher in presenting the material needs to be supported by the role of the parents. Parents need to be given a useful measures facilitate students add information Mathematics is the science of the logic of form, order, magnitude and concepts relate to one another. In concept always related to human life everyday. Learning Mathematics is not just counting from the problem alone but always evolving according to the times, Mathematics subject is the science of counting which aims to inculcate and develop the process of calculation on the students and the curiosity to solve the problems encountered. Based on the observation in SD Pelita 2 West Jakarta, the learning process of teachers still use conventional or teacher-centered teaching methods as the information giver, and the students only listen to the material presented by the teacher so that the students learning outcomes are low. The purpose of community service activities is to improve students learning outcomes by applying process skills in the learning of Mathematics subjects in fourth grade of SD Pelita 2 West Jakarta and to activate students and improve the learning outcomes of fourth graders of SD Pelita 2 West Jakarta through the application of process skills. The subjects of devotion to this community are all Mathematics Teachers and students of grade V SD Pelita 2 West Jakarta. Keywords: process skills, learning outcomes, mathematics AbstrakMatematika adalah ilmu tentang logika mengenai bentuk, susunan, besaran dan konsep berhubungan satu sama lain. Dalam konsepnya selalu berhubungan dengan kehidupan manusia sehari-hari. Belajar Matematika bukan hanya sekedar menghitung dari masalah saja tetapi selalu berkembang sesuai perkembangan zaman, mata pelajaran Matematika adalah ilmu menghitung yang bertujuan untuk menanamkan dan mengembangkan proses hitungan pada siswa serta rasa ingin tahu menyelesaikan masalah yang dijumpai. Berdasarkan hasil observasi di SD Pelita 2 Jakarta Barat, pada proses pembelajaran guru masih menggunakan cara mengajar yang konvensional atau berpusat pada guru sebagai pemberi informasi, dan siswa hanya mendengarkan materi yang disampaikan oleh guru sehingga hasil belajar siswa rendah. Tujuan kegiatan pengabdian kepada masyarakat ini untuk meningkatkan hasil belajar siswa dengan menerapkan keterampilan proses dalam pembelajaran mata pelajaran Matematika di kelas IV SD Pelita 2 Jakarta Barat dan untuk mengaktifkan siswa dan meningkatkan hasil belajar siswa kelas IV SD Pelita 2 Jakarta Barat melalui penerapan keterampilan proses. Subjek pengabdian kepada masyarakat ini adalah seluruh Guru Matematika beserta siswa kelas V SD Pelita 2 Jakarta Barat. Kata kunci: keterampilan proses, hasil belajar, matematika